PENGARUH KESADARAN MEMBAYAR PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN MEMBAYAR PAJAK BUMI DAN BANGUNAN DENGAN PENGETAHUAN PAJAK SEBAGAI PEMODERASI - Rubiyanto, Rubiyanto (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2020)
The purpose of this study is to determine the direct or indirect effects of " Paying Compliance " and "tax penalties " on Compliance Paying "Land and Building Taxes" with "tax knowledge" as a moderating variable. The research method used is the SEM (Structural Equation Modeling) method using MRA (Moderated Regressional Analysis). This research was conducted in Dawarblandong Subdistrict, Mojokerto Regency with a population of 33,945 people. The sample used was 397 respondents. The path analysis results show that "Paying Compliance" and "tax penalties" can directly or indirectly influence Compliance of Paying "Land and Building Tax" with the moderation of "tax knowledge", The magnitude of the direct influence of variable " Paying Compliance" (X1 ) amounting to 0.252 and the variable "tax penalties " (X2) amounting to 0.418, The magnitude of the indirect effect of "tax penalties " (X2) of 0.418 is calculated by transferring the indirect coefficient on the variable, The magnitude of the indirect effect of the variable " Paying Compliance " (X1) is (0.252) X (0.387) = 0.097, while the magnitude of the indirect effect of the variable "tax penalties " (X2) is (0.418) X (0.459) = 0.191, because the magnitude of the value of the direct effect is less than the value of the direct effect, then it can be concluded that the real influence is a direct influence.